Changes in income‐related inequalities in oral health status in Ontario, Canada. Issue 2 (12th October 2020) - Fang, Cheng; Aldossri, Musfer; Farmer, Julie; Gomaa, Noha; Quiñonez, Carlos; Ravaghi, Vahid
Abstract: Objectives: Oral health inequalities impose a substantial burden on society and the healthcare system across Canadian provinces. Monitoring these inequalities is crucial for informing public health policy and action towards reducing inequalities; however, trends within Canada have not been explored. The objectives of this study are as follows: (a) to assess trends in income‐related inequalities in oral health in Ontario, Canada's most populous province, from 2003 to 2014, and (b) to determine whether the magnitude of such inequalities differ by age and sex. Methods: Data representative of the Ontario population aged 12 years and older were sourced from the Canadian Community Health Survey (CCHS) cycles 2003 (n = 36, 182), 2007/08 (n = 36, 430) and 2013/14 (n = 41, 258). Income‐related inequalities in poor self‐reported oral health (SROH) were measured using the Slope Index of Inequality (SII) and Relative Index of Inequality (RII) and compared across surveys. All analyses were sample‐weighted and performed with STATA 15. Results: The prevalence of poor SROH was stable across the CCHS cycles, ranging from 14.1% (2003 cycle) to 14.8% (2013/14 cycle). SII estimates did not change (18.7‐19.0), while variation in RII estimates was observed over time (2003 = 3.85; 2007/08 = 4.47; 2013/14 = 4.02); differences were not statistically significant. SII and RII were lowest among 12‐ to 19‐year‐olds and gradually higher among 20‐ to 64‐year‐olds. RII was slightly higher among females in all survey years. Conclusion: Absolute and relative income‐related inequalities in SROH have persisted in Ontario over time and are more severe among middle‐aged adults. Therefore, oral health inequalities in Ontario require attention from key stakeholders, including governments, regulators and health professionals.